Implementasi Pembelajaran dengan Pendekatan Diferensiasi dalam Matematika - Amelia, Restie; Meiliasari, Meiliasari (Supermat : Jurnal Pendidikan Matematika, 2025)
Differentiation is a popular approach today, especially with the implementation of the independent curriculum. This approach can improve students' cognitive abilities without forcing them to learn in ways that are not essential. The purpose of this study is to identify how differentiation is implemented and evaluate its effectiveness in mathematics learning, as well as to explain the challenges teachers face in applying this approach. The method used was Sistematic Literatur Review (SLR) related to differentiated learning to increase student interest and learning outcomes. The data sources used were 32 articles published in the last three years. The results showed that learning using a differentiated approach had a significant impact on students' cognitive abilities, as indicated by their interest, activity, and learning outcomes. During implementation, there are several things that teachers must pay attention to, namely that teachers must design learning activities as effectively as possible and conduct diagnostic assessments at the beginning of the activity. Challenges in implementing differentiated learning also exist, namely time, managing thoughts and bodies in providing guidance to students, preparing adequate learning resources and media for all learning styles of each student, and teachers must be open to developments